2017
DOI: 10.2147/cmar.s139889
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell PD-L1 predicts poor local control for rectal cancer patients following neoadjuvant radiotherapy

Abstract: The tumor cell (TC) PD-L1 expression has been reported by several studies in various types of cancer, and it reduces the cytotoxicity of T-cells toward cancer and evades the anticancer immune response. Herein, our study focuses on the impact of PD-L1 expression in prognosis and the correlation with clinical prognostic factors for local advanced rectal cancer with neoadjuvant radiotherapy (RT). A total of 68 rectal cancer patients treated with neoadjuvant RT were retrospectively enrolled in the present study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Our study showed the expression difference of LAG-3 and CD8 between the LCRT and SCRT, suggesting that some ICBs and TILs might be modified by the treatment regimens. In accordance with these results, PD-L1 expression in TCs was mostly positive in the SCRT subgroup in our previous study [22]. mmation might be induced by the radiotherapeutic dose and fractionation, also the chemotherapy alongside the LCRT was a consideration.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed the expression difference of LAG-3 and CD8 between the LCRT and SCRT, suggesting that some ICBs and TILs might be modified by the treatment regimens. In accordance with these results, PD-L1 expression in TCs was mostly positive in the SCRT subgroup in our previous study [22]. mmation might be induced by the radiotherapeutic dose and fractionation, also the chemotherapy alongside the LCRT was a consideration.…”
Section: Discussionsupporting
confidence: 89%
“…We found no effect of short-course versus long-course RT on PD-L1+ cells. Shao et al reported, in a retrospective study of 68 rectal cancer patients treated with neoadjuvant RT, that tumor cells PD-L1+ was significantly correlated to short-course RT, suggesting that PD-L1 expression might be regulated by modifying the RT scheme [ 35 ]. This would allow the addition of an immune checkpoint inhibitor targeting PD-1/PD-L1 axis in the adjuvant setting.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the inclusion criteria, 15 articles were finally eligible for the meta-analysis. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] A total of 3078 patients from China, South Korea, USA, Japan, Switzerland, and Germany were enrolled. Sample sizes of the studies ranged from 60 to 456 cases.…”
Section: Search Resultsmentioning
confidence: 99%
“…3 Where PD-L1 is expressed may produce different findings. Although previous studies have confirmed that high expression of PD-L1 on TCs was linked with worse survival in CRC patients, 22,31 only a few studies have examined the association between PD-L1 expression on TIICs and prognosis in CRC patients. Recently, two studies revealed that high PD-L1 expression on TIICs was associated with a favorable prognosis in CRC patients.…”
Section: Discussionmentioning
confidence: 99%